Outsourcing: Risks and Impact to Service Quality within European Investment Banks - Tomlinson, Michael J (2015)
Since the financial crash of 2008, an extensive number of fines have been imposed on the investment banks for episodes of business misconduct and rigging of the financial markets, and there has been little evidence to suggest that the banks themselves are taking the necessary precautions to control fundamental issues within the sector, with subsequent loss of trust and wider speculation that the banks are placing profits before client needs. The banks have had to rethink their processes through the outsourcing of their daily operations to drive down costs, and make business units profitable once again. Literature is divided as to the benefits of outsourcing, with an underlying theme that it creates a number of risks to firms. With this in mind, the study assumes that outsourcing may precipitate numerous risks, which can ultimately impact service quality, and expose the banks to greater risk overall. The study aims, by means of open questionnaires, to understand the risks and impact that outsourcing creates in relation to service quality within European investment banks, and as such assists in closing the gap in the literature between outsourcing risks and service quality dimensions. Findings indicate that outsourcing does indeed expose the banks to a number of risks, all of which directly impact service quality. Control mechanisms appear to be in place, but further restrictions and governance is required. In particular it is recognised that the control of core competencies such as operational knowledge, as well as ethical risks, and cultural differences, require further regulation. It is therefore recommended that there is greater collaboration between the outsourced firms and banking entities, in order to mitigate the risks that fundamentally impact service quality and the banks as a whole.